2016
DOI: 10.1063/1.4952876
|View full text |Cite
|
Sign up to set email alerts
|

An energy dispersive bent Laue monochromator for K-edge subtraction imaging

Abstract: A tunable Laue/bent-Laue monochromator with fixed second crystal for synchrotron radiation AIP Conference Proceedings 417, 95 (1997) Abstract. K-Edge Subtraction (KES) is a powerful synchrotron imaging method that allows the quantifiable determination of a contrast element (e.g. iodine) and matrix material (usually represented as water) in both projection imaging and computed tomography. A bent Laue monochromator has been developed that has very good focal and energy dispersive properties for KES. Approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, energy resolution measures the quality of the energetic spatial dispersion, which in turn determines the blur of the detected Kedge along the energy axis. A large energy blurring negatively affects the material decomposition as a relevant portion of the field-of-view is occupied by edge-crossing energies (Samadi et al 2016). Additionally, a poor energy resolution does not allow the detection of subtle near-edge attenuation features, thus preventing the implementation of near-edge spectroscopy techniques such as EXAFS (Qi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, energy resolution measures the quality of the energetic spatial dispersion, which in turn determines the blur of the detected Kedge along the energy axis. A large energy blurring negatively affects the material decomposition as a relevant portion of the field-of-view is occupied by edge-crossing energies (Samadi et al 2016). Additionally, a poor energy resolution does not allow the detection of subtle near-edge attenuation features, thus preventing the implementation of near-edge spectroscopy techniques such as EXAFS (Qi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it has been demonstrated that by choosing asymmetrically cut crystals matching a focusing criterion referred to as magic condition (Martinson et al 2015, Qi et al 2021 optimal energy resolution can be reached. The understanding of the magic condition has paved the way for SKES, bringing a significant reduction of edge-crossing energies (from around 30% to a few % of the field-of-view), and removing the need for beam splitters (Samadi et al 2016).…”
Section: Introductionmentioning
confidence: 99%